Sox13 functionally complements the related Sox5 and Sox6 as important developmental modulators in mouse spinal cord oligodendrocytes. Issue 2 (25th November 2015) - Baroti, Tina; Schillinger, Anja; Wegner, Michael; Stolt, C. Claus
Abstract: The role of transcription factor Sox13, which together with Sox5 and Sox6 belongs to the SoxD family, is only poorly characterized in central nervous system development. Therefore, we analysed whether Sox13 expression and function overlaps with or differs from that of its close relatives Sox5 and Sox6. In the developing mouse spinal cord, we found Sox13 predominantly expressed in neuroepithelial precursors, oligodendroglial and astroglial cells. The substantially overlapping expression with Sox5 and Sox6 in oligodendroglial cells prompted us to study potential roles during specification, lineage progression and differentiation of oligodendrocytes. In contrast to Sox5 and Sox6, Sox13 expression continues after differentiation and even increases in myelinating oligodendrocytes. Sox13 deletion did not interfere with oligodendroglial development, which was normal in Sox13‐deficient mice. However, the premature differentiation of oligodendrocyte precursors triggered by loss of Sox6 was slightly more prominent in Sox6/Sox13 double‐deficient mice. Sox13 can bind to the same sites in myelin gene promoters as Sox5 and Sox6 in vitro . Reporter gene assays furthermore reveal a similar antagonizing effect on Sox10‐dependent transactivation of myelin gene promoters as previously shown for Sox5 and Sox6. This argues that Sox13 is functionally redundant with the other SoxD proteins and complements Sox5 and Sox6 in their role as important modulators of oligodendrocyte development. The transcription factor Sox13 is co‐expressed with the related Sox5 and Sox6 in cells of the oligodendroglial lineage. By itself, it has little impact on oligodendrocyte development but supports Sox5 and Sox6 during the process as a functionally redundant transcription factor. Abstract : The transcription factor Sox13 is co‐expressed with the related Sox5 and Sox6 in cells of the oligodendroglial lineage. By itself, it has little impact on oligodendrocyte development but supports Sox5 and Sox6 during the process as a functionally redundant transcription factor.